Atypical long-latency auditory event-related potentials in a subset of children with specific language impairment. - Bishop, D; Hardiman, M; Uwer, R; von Suchodoletz, W (2007)
It has been proposed that specific language impairment (SLI) is the consequence of low-level abnormalities in auditory perception. However, studies of long-latency auditory ERPs in children with SLI have generated inconsistent findings. A possible reason for this inconsistency is the heterogeneity of SLI. The intraclass correlation (ICC) has been proposed as a useful statistic for evaluating heterogeneity because it allows one to compare an individual's auditory ERP with the grand average waveform from a typically developing reference group. We used this method to reanalyse auditory ERPs from a sample previously described by Uwer, Albrecht and von Suchodoletz (2002). In a subset of children with receptive SLI, there was less correspondence (i.e. lower ICC) with the normative waveform (based on the control grand average) than for typically developing children. This poorer correspondence was seen in responses to both tone and speech stimuli for the period 100-228 ms post stimulus onset. The effect was lateralized and seen at right- but not left-sided electrodes.